2010
DOI: 10.1002/bit.22988
|View full text |Cite
|
Sign up to set email alerts
|

Improved galactose fermentation of Saccharomyces cerevisiae through inverse metabolic engineering

Abstract: Although Saccharomyces cerevisiae is capable of fermenting galactose into ethanol, ethanol yield and productivity from galactose are significantly lower than those from glucose. An inverse metabolic engineering approach was undertaken to improve ethanol yield and productivity from galactose in S. cerevisiae. A genome-wide perturbation library was introduced into S. cerevisiae, and then fast galactose-fermenting transformants were screened using three different enrichment methods. The characterization of geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 35 publications
6
49
0
Order By: Relevance
“…All of these observations suggested the need for identifying effective gene targets through methods that directly select resistant yeast strains with traceable genetic perturbations. Successful application of inverse metabolic engineering in the present study and some previous works (34,(61)(62)(63)(64) demonstrated the effectiveness of this approach in discovering novel gene perturbation targets for improving the desirable target phenotypes.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…All of these observations suggested the need for identifying effective gene targets through methods that directly select resistant yeast strains with traceable genetic perturbations. Successful application of inverse metabolic engineering in the present study and some previous works (34,(61)(62)(63)(64) demonstrated the effectiveness of this approach in discovering novel gene perturbation targets for improving the desirable target phenotypes.…”
Section: Discussionsupporting
confidence: 69%
“…The genomic DNA of the S. cerevisiae S288C strain was used to construct the genomic library as previously described (34). Briefly, genomic DNA fragments (2 to 5 kb) were generated by sonication and ligated into a multicopy plasmid, pRS424 (a yeast episomal plasmid), with TRP1 as an auxotrophic selection marker (35,36).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study we inferred that the identified mutations in the Ras/PKA signaling pathway may have triggered the upregulation of PGM2 and reserve carbohydrates metabolism because not only were the mutations identified in all of the evolved mutants but also on the promoter region of PGM2, and genes involved in reserve carbohydrate metabolism contained STER elements involved in Ras activation (27). The upregulation of PGM2 in the evolved strains could increase galactose utilization as proven in earlier studies (3,13,17,21). In the present study, the mutations RAS2 Lys77 (RAU) and RAS2 Tyr112 (RBU) showed a certain relation to the upregulation of PGM2 but not to any changes in reserve carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 68%
“…The modification targets to improve galactose utilization have been well elucidated in S. cerevisiae, which include engineering of the regulatory network (inactivation of repressors and up-regulation of activator) and overexpression of the final enzyme, phosphoglucomutase (PGM2) in the Leloir pathway responsible for galactose catabolism [75][76][77]. All these targets were directly associated with the galactose metabolic pathway, but using a cDNA library, another target that is not part of galactose metabolism was also found [71]. In this study, three beneficial over-expression targets, SEC3, tTUP1, and SNR84 were identified.…”
Section: Extended Substrate Rangementioning
confidence: 99%